How to Regulate an illegal platform in P2P Lending? (Evidence From Indonesia and Global Approach) - Suryono, Arief; Kharisma, Dona Budi; Wanda Yunitha Purba, Agata (Faculty of Law, Universitas Pekalongan, 2024)
The aim of this studi is: (1) to scrutinize the legal predicaments pertaining to the governance of Peer-to-Peer (P2P) lending in Indonesia, by drawing comparisons with the regulatory frameworks of the United States and the United Kingdom, and (2) to devise the optimal legal mechanism for the regulation of P2P lending transactions. This study employs a normative legal research methodology utilizing comparative and legal approaches to investigate the regulatory frameworks for P2P lending in Indonesia, the United States, and the United Kingdom. The legal materials used in this study solely pertain to P2P lending regulations and were collected using library research techniques. The expansion of P2P lending in Indonesia has been impeded by the widespread prevalence of unlawful P2P lending practices. A comparative evaluation of the regulatory structures of the United States and the United Kingdom highlights that the insufficiency of regulatory measures has played a role in aggravating this issue. The UK's well-structured and comprehensive regulations, which provide robust protections, are worth emulating and implementing, especially considering that P2P lending in the UK is successful and dominates the European economic market. Meanwhile, the strict information disclosure and platform registration rules implemented in P2P lending in the United States are essential regulatory factors that the OJK should consider in its supervision of P2P lending in Indonesia.